2003
DOI: 10.1161/01.cir.0000055187.67365.81
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Diazoxide Is Mediated by Activation of Sarcolemmal but Not Mitochondrial ATP-Sensitive Potassium Channels in Mice

Abstract: Background-We recently demonstrated that the sarcolemmal ATP-sensitive potassium (sarcK ATP ) channel plays a key role in cardioprotection against ischemia/reperfusion injuries in Kir6.2-knockout (KO) mice. In the present study, we evaluated the effects of diazoxide, a mitochondrial ATP-sensitive potassium (mitoK ATP ) channel opener, on ischemiainduced myocardial stunning in sarcK ATP channel-deficient mice. Methods and Results-Langendorff-perfused hearts of wild-type (WT) and KO mice were subjected to global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 15 publications
1
87
2
Order By: Relevance
“…One suggested mechanism for the antioxidant activity characteristics of nicorandil is the role of mt-KATP channels. Although some investigations suggest that mt-KATP channels have a role in ischemic preconditioning, especially in intestinal tissue [24], there are others who question this property [45,46]. For instance, one suggested mechanism to explain ischemic preconditioning in cardiac tissue is involvement of sarcolemmal KATP channels rather than mt-KATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…One suggested mechanism for the antioxidant activity characteristics of nicorandil is the role of mt-KATP channels. Although some investigations suggest that mt-KATP channels have a role in ischemic preconditioning, especially in intestinal tissue [24], there are others who question this property [45,46]. For instance, one suggested mechanism to explain ischemic preconditioning in cardiac tissue is involvement of sarcolemmal KATP channels rather than mt-KATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…This issue was recently readdressed in Kir6.2 knockout mice [71,72]. The knockout mice displayed a blunted response to IPC, and their hearts went into contracture within 5 min of exposure to ischemia and did not recover function during reperfusion.…”
Section: Role Of Surface K Atp Channelmentioning
confidence: 99%
“…We thank Drs Duncker and Verdouw for their interest in our article 1 and their comments with respect to the interpretation of the results.…”
Section: Responsementioning
confidence: 97%
“…The findings of the study suggested that activation of sarcolemmal K ATP channels rather than mitochondrial K ATP channels is important for the cardioprotective effect of diazoxide in mouse hearts. 1 We measured the left ventricular function during 20-minute ischemia followed by 60-minute reperfusion and found that diazoxide improved the contractile dysfunction in wildtype but not Kir6.2 knockout hearts. The stunned myocardium is defined as "prolonged postischemic contractile dysfunction of myocardium salvaged by reperfusion."…”
Section: Responsementioning
confidence: 99%